2023
DOI: 10.4018/jgim.318694
|View full text |Cite
|
Sign up to set email alerts
|

The Moderation Role of AI-Enabled Service Quality on the Attitude Toward Fitness Apps

Abstract: Artificial intelligent technology is rapidly transforming the fitness apps landscape by applying data mining technologies within given parameters. These wide-ranging AI-enabled services improve user interface and enhance customers' experience when exercising with the fitness apps. The current study integrated the four antecedents—technological functions, intrinsic information quality, perceived enjoyment, and social connection—to investigate the moderating influence of AI-enabled service quality on users' atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Users are more likely to adopt positive attitudes toward technologies if they find interaction with them enjoyable. For instance, research on AI-enabled fitness apps suggests that the perceived enjoyment derived from using these apps positively influences individuals’ attitudes towards them [ 44 ]. With regard to education field, an investigation encompassing 317 graduates and undergraduates showed that the perceived enjoyment positively influenced the attitudes towards the application of ICTs in higher education learning environments in Saudi Arabia [ 45 ].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Users are more likely to adopt positive attitudes toward technologies if they find interaction with them enjoyable. For instance, research on AI-enabled fitness apps suggests that the perceived enjoyment derived from using these apps positively influences individuals’ attitudes towards them [ 44 ]. With regard to education field, an investigation encompassing 317 graduates and undergraduates showed that the perceived enjoyment positively influenced the attitudes towards the application of ICTs in higher education learning environments in Saudi Arabia [ 45 ].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Measurement methods from the previous literature were adopted [42,53]; detailed information on the measurement items is provided in Table 2. The means of the construct reflected the consumers' perceptions of the construct: social equity (Mean = 3.737), perceived value (M = 3.471), identification (M = 3.927), design attributes (M = 4.093), shared attributes (M = 4.078), naturalness (M = 3.754), and safety (M = 3.897), as shown in Table 2.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…A randomly selected subsample was used over 5000 iterations employing overlays to estimate the hypothesized relationships [51]. For the corresponding endogenous constructs, Stone-Geisser's Q 2 was used to assess the predictive relevance of the endogenous constructs [53]. The results indicated that the Q 2 values for identification (0.133) and acceptance (0.080) exceeded the recommended thresholds (>0) [52].…”
Section: Structural Modelmentioning
confidence: 99%
“…The total experience a customer has with a store is based on their encounters with and views about the brand (Oh et al, 2012;Verhoef et al, 2009;Tseng et al, 2023). According to Ameen et al (2021), the application of AI technologies, such as machine learning, natural-language comprehension, and naturallanguage processing, may assist in analyzing consumer sentiment and feedback at scale, precision, and speed that humans cannot achieve.…”
Section: Artificial Intelligence-enabled Customer Experiencementioning
confidence: 99%